Brexit and Devolution in the United Kingdom - Keating, Michael (2017)
Devolution in the United Kingdom is deeply connected to United Kingdom membership of the European Union, which provides an external support system for the internal settlement. Exit from the European Union destabilizes the internal settlement and raises a series of major constitutional issues.